(untitled) (Journal of the College of Education for Women, 2019)
Many approaches of different complexity already exist to edge detection incolor images. Nevertheless, the question remains of how different are the resultswhen employing computational costly techniques instead of simple ones. Thispaper presents a comparative study on two approaches to color edge detection toreduce noise in image. The approaches are based on the Sobel operator and theLaplace operator. Furthermore, an efficient algorithm for implementing the twooperators is presented. The operators have been applied to real images. The resultsare presented in this paper. It is shown that the quality of the results increases byusing second derivative operator (Laplace operator). And noise reduced in a goodrange by using mean filter for smoothing before applying Laplace operator.Moreover, thresholding is used for image in both cases to see results in clearermanner.